Analisis Standar Penilaian Pendidikan Pada Pendidikan Dasar Dan Menengah Di Indonesia - Khamim Khamim (Pascasarjana Institut Ilmu Al Quran (IIQ) Jakarta, 2019)
Standar Penilaian Pendidikan is a part of Standar Nasional Pendidikan, where the form of explanation is from mandate of Undang-undang Nomor 20 Tahun 2003 concerning Sistem Pendidikan Nasional. The educators should understand on standar penilaian pendidikan, and know the background juridicial foundation of standar penilaian, mechanism, configuration, and evaluation procedure. Product of law is related to penilaian pendidikan, has set how is mechanism, configuration, education assessment instrument from SD, SMP, SMA, and University. With understanding the juridicial foundation which is related to education assessment, so educators must have a role to lead education quality that has been standared, so the destination of education in Indonesia can be realized.